The ADP-Ribosylating Toxins of Salmonella - Rachel A. Cheng; Martin Wiedmann (Toxins, 2019)
A number of pathogenic bacteria utilize toxins to mediate disease in a susceptible host. The foodborne pathogen Salmonella is one of the most important and well-studied bacterial pathogens. Recently, whole genome sequence characterizations revealed the presence of multiple novel ADP-ribosylating toxins encoded by a variety of Salmonella serovars. In this review, we discuss both the classical (SpvB) and novel (typhoid toxin, ArtAB, and SboC/SeoC) ADP-ribosylating toxins of Salmonella, including the structure and function of these toxins and our current understanding of their contributions to virulence.